Diode laser ablation of a tracheal osteochondroma in a dog. (26th April 2016) - Bottero, E.; Cagnasso, A.; Gianella, P.
Abstract : A mass almost completely obstructing the tracheal lumen was detected during endoscopic investigation of dyspnoea in a four‐month‐old golden retriever. Histopathology was consistent with osteochondroma. The lesion was ablated using endoscopic diode laser ablation.